Arab Republic of Egypt : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2005)
This Selected Issues paper on the Arab Republic of Egypt examines the dynamic relationship between the nominal exchange rate and prices during Egypt's exit from a managed exchange rate regime. The exit from the peg went through several phases, including a series of step devaluations between 2000 and 2002, a first attempt at a float in January 2003, and the successful transition to a unified, flexible exchange rate system in late-2004. From 2000 to 2004, the Egyptian pound experienced a cumulative depreciation of 68 percent against the U.S. dollar.